Challenges and opportunities in the risk assessment of existing substances in Canada: lessons learned from the international community. (2017) - Barton-Maclaren, Tara S.; Westphal, Margit; Sarwar, Elaha; Mattison, Donald; Chiu, Weihsueh A.; Dix, David; Kavlock, Robert; Krewski, Daniel
The evaluation and regulation of chemical substances have undergone a major overhaul in Canada, the USA and the European Union (EU) over the last decade. To facilitate increasing concerns over chemical safety, changes in regulations and strategic plans were introduced. Specifically, the Canadian parliament adopted a new amendment to the Canadian Environmental Protection Act (CEPA) in 1999, the US National Academy of Sciences published the 2007 NRC report TT21C, the US EPA developed the Strategic Plan in 2009, and the EU introduced new legislation in 2007 called Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH substances). A 2013 workshop held in Ottawa (Risk Sciences International) focused on regulatory issues and challenges faced by these nations. This review summarises many of the discussions held during the workshop and specifically, five challenges that Canada has encountered when assessing chemicals with limited data on Canada's Domestic Substances List (DSL).